Oxford Research Encyclopedia of Psychology 2017
DOI: 10.1093/acrefore/9780190236557.013.210
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Personality Traits

Abstract: The physical, psychological, and economic benefits of regular moderate-to-vigorous-intensity physical activity are well substantiated. Unfortunately, few people in developed countries engage in enough physical activity to reap these benefits. Thus, a strong theoretical understanding of what factors are associated with physical activity is warranted in order to create effective and targeted interventions. Social/ecological approaches to understanding physical activity demonstrate the breadth of correlates that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 0 publications
1
20
1
1
Order By: Relevance
“…Journal Sport Area http://journal.uir.ac.id/index.php/JSP Personality is one of the concepts in psychological science that is very important and is the key to the success or failure of students in undergoing academic activities both at the elementary school and at university level (Hakimi et al, 2011;Prakash, Singh, & Yadav, 2016). Personality basically has a meaning as a behavior, habit, nature, character, character which is the hallmark of an individual (Aşçi, Lindwall, Altintaş, & Edepli Gürsel, 2015;Rhodes & Boudreau, 2017). A person's personality is determined by two factors, namely heredity and environment, where both of these factors will play a role in producing a good or bad personality (Baro & Buragohain, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Journal Sport Area http://journal.uir.ac.id/index.php/JSP Personality is one of the concepts in psychological science that is very important and is the key to the success or failure of students in undergoing academic activities both at the elementary school and at university level (Hakimi et al, 2011;Prakash, Singh, & Yadav, 2016). Personality basically has a meaning as a behavior, habit, nature, character, character which is the hallmark of an individual (Aşçi, Lindwall, Altintaş, & Edepli Gürsel, 2015;Rhodes & Boudreau, 2017). A person's personality is determined by two factors, namely heredity and environment, where both of these factors will play a role in producing a good or bad personality (Baro & Buragohain, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Learning and developing physical abilities involves engaging in actions whose levels of activity are high, but also an active lifestyle that allows them to crystallize those abilities. The superiority of the activity manifestation in the case of increased extraversion is a determining factor for initiation and involvement in physical activities ( Rhodes & Boudreau, 2019). Extraversion is positively associated with aerobic activities as well as the active environments of the activity unfolding such as swimming, dancing, or tennis, though there are no significant differences in other sporting activities such as running or cycling.…”
Section: Resultsmentioning
confidence: 99%
“…First, we found that, compared to girls who were reported as being less engaged by their teachers, girls who completed work on time and independently, demonstrated self-confidence, and were able to solve daily problems on their own were more likely to take part in physical activity in their leisure time, including sport. Practicing frequent physical activity, even during leisure time, requires self-discipline, especially during adolescence and adulthood ( Bogg and Roberts, 2004 , Rhodes and Boudreau, 2017 , Wilson and Dishman, 2015 ). Thus, girls who have developed and demonstrated self-discipline in the classroom may find it easier to engage in sport at age 12 years, a developmental period where such interest declines ( CFLRI, 2019 , Kemp et al, 2019 , Zimmerman-Sloutskis et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%